Impact of stoma site marking on healthcare costs in patient care - Silva, Patricia Rosa da; Alemão , Márcia Mascarenhas; Araújo, Meiriele Tavares; Borges, Eline Lima; Alonso, Claudiomiro da Silva (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To analyze the impact of stoma site marking on healthcare costs for patients who underwent marking and those who did not, as well as the subsequent outcomes. Method: We conducted an economic evaluation in healthcare based on retrospective primary data. We obtained the data from the medical records of patients treated at the Health Care Service for Ostomy Patients in Belo Horizonte, Minas Gerais, Brazil, between 2015 and 2021. The sample consisted of 40 patients, with 20 who underwent stoma site marking and 20 who did not. We applied the Mann-Whitney test for independent samples and analyzed the effect size, which was adjusted using Hedge’s g test, considering the risk of low sample power. Results: The study identified an average cost of R5,201.47 (US938.19) for the group of patients who did not undergo stoma site marking, which was 23.88% higher than the cost of R3,959.27 (US938.19) for the group who did. Most patients were female, with an average age of 60.7 years, married, and of mixed race. Colorectal cancer was the most common cause of stoma creation, while dermatitis was the most frequent complication. We observed that complications led to increased costs. Conclusion: Stoma site marking significantly affects the healthcare costs for individuals with elimination stomas.